Respuesta :

Answer:

1.  - 2f , 2 - 6f , 3 - 13 f, and fnally  14 f

Step-by-step explanation:

1.  Re-order terms so constants are on the left

f (-2)

-2 f

2.  Move  

6

to the left of  

f.

3. Re-order terms so constants are on the left

f  (-13)

-13f

Answer:

f(-2) = 13

f(6) = 19

f(-13) = 52

f(-14) = 56

Step-by-step explanation:

Hi! This question topic is functions. Let me break it down to you.

f(x)  = |5 - 4x| is the same as y = |5-4x| I think you may be familiar with y = mx + b equations.

f(x) is trying to say that you should replace x with the number in f(_) in the equation. You'll get it when we start solving

Question 1 : f(-2)

We replace -2 in the equation

f(-2) = |5 - 4(-2)|

f(-2) = |5 +8|      =>   Remember, negative x negative = positive

f(-3) = 13            => Absolute Value, positive stays positive, negative turns positive

Question 2 : f(6)

We replace 6 in the equation

f(6) = |5 - 4(6)|

f(6) = |5 - 24|

f(6) = |-19|          => Turns poitive!

f(6) = 19

Question 3 : f(-13)

We replace -13 in the equation

f(-13) = |5 - 4(-13)|

f(-13) = |5 +52|

f(-13) = |57|

f9-13) = 57

Question 4 : f(-14)

We replace -14 in the equation

f(-14) = |5 - 4(-14)|

f(-14) = |5 + 56|

f(-14) = |61|

f(-14) = 61

-Chetan K